2005
DOI: 10.1523/jneurosci.2818-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-Inducing Factor Triggered by Poly(ADP-Ribose) Polymerase and Bid Mediates Neuronal Cell Death after Oxygen-Glucose Deprivation and Focal Cerebral Ischemia

Abstract: Delayed neuronal cell death occurring hours after reperfusion is a hallmark of ischemic stroke and a primary target for neuroprotective strategies. In the present study, we investigated whether apoptosis-inducing factor (AIF), a caspase-independent proapoptotic protein, is responsible for neuronal cell death after glutamate toxicity and oxygen-glucose deprivation (OGD) in vitro and after experimental stroke in vivo. AIF translocated to the nucleus in which it colocalized with DNA fragmentation and nuclear apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
275
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(296 citation statements)
references
References 49 publications
18
275
3
Order By: Relevance
“…5,19 The pivotal role for Bid upstream of such mitochondrial dysfunction is substantiated by experiments demonstrating pronounced neuroprotective effects of the Bid inhibitor BI-6c9 in models of glutamate-induced excitotoxicity and OGD in primary cultured neurons, and similar studies in HT-22 neurons using Bid siRNA. 19,20,30,31 Further, reduced Bid expression attenuated neuronal death in a model of OGD in vitro and reduced brain damage in models of cerebral ischemia and brain trauma in vivo. 21 Recent studies showed that tBid and full-length Bid exert similar effects on mitochondria and AIF-dependent cell death in neurons.…”
Section: Discussionmentioning
confidence: 92%
“…5,19 The pivotal role for Bid upstream of such mitochondrial dysfunction is substantiated by experiments demonstrating pronounced neuroprotective effects of the Bid inhibitor BI-6c9 in models of glutamate-induced excitotoxicity and OGD in primary cultured neurons, and similar studies in HT-22 neurons using Bid siRNA. 19,20,30,31 Further, reduced Bid expression attenuated neuronal death in a model of OGD in vitro and reduced brain damage in models of cerebral ischemia and brain trauma in vivo. 21 Recent studies showed that tBid and full-length Bid exert similar effects on mitochondria and AIF-dependent cell death in neurons.…”
Section: Discussionmentioning
confidence: 92%
“…In experimental stroke, both nNOS and PARP activity were found to be increased (Eliasson et al, 1997;Endres et al, 1997;Eliasson et al, 1999;Goyagi et al, 2003), and gene deletion or pharmacologic inhibition of nNOS or PARP-1 reduced infarct volume (Huang et al, 1994;Eliasson et al, 1997;Endres et al, 1997;Goto et al, 2002). In addition, inhibition of PARP decreased AIF translocation, and knockdown of AIF in Harlequin mice reduced infarct volume after 45 minutes of MCAO (Culmsee et al, 2005). Direct exposure of cultured neurons to peroxynitrite stimulates AIF translocation (Zhang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This design permitted evaluation at early reperfusion, at a mid-range of reperfusion, when many neurons show ischemic morphologic changes, and at late reperfusion, when cell death is widespread throughout the maturing infarct. These timepoints spanned the 1-8 hour range for AIF translocation reported by others (Ferrer et al, 2003;Plesnila et al, 2004;Zhao et al, 2004;Culmsee et al, 2005). Two hemispheres were used per lane.…”
Section: Subcellular Fractionation and Immunoblottingmentioning
confidence: 99%
See 2 more Smart Citations